2022
DOI: 10.1155/2022/4197473
|View full text |Cite|
|
Sign up to set email alerts
|

Adipose-Derived Mesenchymal Stem Cell-Derived Extracellular Vesicles Rescue Tendon Injury in Rat via the miR-19 a/IGFBP3 Axis

Abstract: Purpose. Adipose-derived mesenchymal stem cells (ADSCs) are increasingly applied in tendon repair. However, the underlying mechanisms of ADSC-derived extracellular vesicles (EVs) in tendon healing are largely unknown. In this study, we investigated the effect of the EVs secreted by ADSCs on the recovery of tendon injuries and its potential mechanism. Materials and Methods. We injected ADSCs into the injured tendon, followed by the evaluation of the tissue morphology, tenocyte proliferation, and oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(38 citation statements)
references
References 45 publications
(46 reference statements)
0
38
0
Order By: Relevance
“…After searching the six databases, a total of 1794 studies were found. Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After searching the six databases, a total of 1794 studies were found. Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies had a low risk of baseline characteristics under selection bias, random outcome assessment under detection bias, attrition bias, reporting bias, and other biases [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. All studies reported baseline characteristics of the animals used which included the species, age and gender of the animals, and the outcomes were randomly assessed [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%